Gobernar es educar - Oscar Arias-Sánchez (Universidad Nacional, Costa Rica, 2001)
Education plays a critical role in the reduction of the most prominent enemy of peace, democracy, and human development: poverty. It is the catalyst of the constructive participation in the social and political processes of those groups traditionally silenced and excluded from development. Education is particularly important in a global society. It is a fundamental factor to understand the pluralism of the nations and their cultural diversity. It contributes to the national and regional integration. Education, viewed as everyone's responsibility, should not only be aimed at instructing and training individuals for the labor market, but also at educating them in a series of principles and values. In so doing, educating by the example should play a major role. The author concludes stressing the importance that participation in politics becomes a pedagogical practice. Politicians should become educators capable of generating knowledge for themselves and the people they represent. They should model with their example the principles the preach. To do politics and govern is to educate.